2021
DOI: 10.1021/acsaem.0c03015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Thermally Electrochemically Activated β-PVDF Fiber on Suppression of Li Dendrite Growth for Anode-Free Batteries

Abstract: Organic electrolytes react aggressively with lithium (Li) active materials, especially at 60 °C, exhibiting uncontrolled dendrite growth. Herein, β-poly­(vinylidene difluoride) (PVDF) polymer conformal coating on copper (Cu) is successfully prepared via electrospinning. The charge/discharge performance of the anode-free full cell configuration, either Cu@β-PVDF∥NMC or Cu@α-PVDF∥NMC, is very poor at room temperature. Interestingly, when the Cu@β-PVDF∥NMC cell treated with five charge/discharge cycles at 60 °C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 43 publications
(64 reference statements)
0
22
0
Order By: Relevance
“…Moreover, the initial dip of the potential, which is known to arise due to the energy barrier for lithium nucleation, was found to be the smallest for the electrode coated with LiF@PVDF, indicating the correlation between the coating medium and the lithium deposition kinetics. , It is supposed that the high-dielectric medium homogenizes the electric field at the interface and mitigates the locally high-current-density region, thus reducing the overall interface overpotential. Note that the surface analysis results reveal that the SEI component on Cu foils after cycling is almost identical regardless of PVDF coatings as shown in Figure S12, which rules out any potential impact of altered SEI structure by side reactions of PVDF with Li metals . The consequence of the low interface overpotential could be examined on the distinct lithium deposition behavior by the simple comparative simulation in Figure c.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, the initial dip of the potential, which is known to arise due to the energy barrier for lithium nucleation, was found to be the smallest for the electrode coated with LiF@PVDF, indicating the correlation between the coating medium and the lithium deposition kinetics. , It is supposed that the high-dielectric medium homogenizes the electric field at the interface and mitigates the locally high-current-density region, thus reducing the overall interface overpotential. Note that the surface analysis results reveal that the SEI component on Cu foils after cycling is almost identical regardless of PVDF coatings as shown in Figure S12, which rules out any potential impact of altered SEI structure by side reactions of PVDF with Li metals . The consequence of the low interface overpotential could be examined on the distinct lithium deposition behavior by the simple comparative simulation in Figure c.…”
mentioning
confidence: 86%
“…Note that the surface analysis results reveal that the SEI component on Cu foils after cycling is almost identical regardless of PVDF coatings as shown in Figure S12, which rules out any potential impact of altered SEI structure by side reactions of PVDF with Li metals. 75 The consequence of the low interface overpotential could be examined on the distinct lithium deposition behavior by the simple comparative simulation in Figure 5c. The numerical simulation was carried out considering the interface medium during the lithium deposition (Figure S13), when different effective overpotentials were applied with 0.1 and 0.3 V. It is shown that the lithium conformally grows on the initial triangular shape of the current collector at a 0.1 V overpotential, while the lithium deposits in irregular shapes, plating the current collector nonuniformly at 0.3 V overpotential.…”
mentioning
confidence: 99%
“…Abrha et al successfully prepared the β-polyvinylidene fluoride (PVDF) polymer conformal coated Cu by electrostatic spinning, which showed stable cycle performance. [102] Polar β-PVDF is considered to be effective in directing lithium ions flux, and this excellent performance results from the reaction between β-PVDF and deposited lithium metal to form a strong, LiF-rich SEI.…”
Section: Modification Of the Interfacementioning
confidence: 99%
“…2 This protocol also gives reliable information about the irr-CE sources that could be attributed to SEI formation, electrolyte decomposition, and dead Li formation. 16,19,23,34,35 To extract reliable information related to the irreversible reactions (irr-rxns) at the cathode surface, the cathode||Li cell configuration is an efficient protocol. Reliable information regarding the first irreversible capacity, cathode electrolyte interface (CEI), cathode degradation, and oxidative electrolyte decomposition at the cathode surface can be extracted from the cathode||Li cell configuration.…”
Section: Introductionmentioning
confidence: 99%
“…However, by substituting the working electrode of Li by Cu in the Li||Cu cell configuration, the irreversible sources on the bare Cu electrode surface are easily quantified . This protocol also gives reliable information about the irr-CE sources that could be attributed to SEI formation, electrolyte decomposition, and dead Li formation. ,,,, To extract reliable information related to the irreversible reactions (irr-rxns) at the cathode surface, the cathode||Li cell configuration is an efficient protocol. Reliable information regarding the first irreversible capacity, cathode electrolyte interface (CEI), cathode degradation, and oxidative electrolyte decomposition at the cathode surface can be extracted from the cathode||Li cell configuration. However, it is impossible to quantify the irr-CE sources at the anode electrode in this protocol.…”
Section: Introductionmentioning
confidence: 99%